2016
DOI: 10.1002/ange.201603810
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐induced Substitutive Introduction of the Aldoxime Functional Group to Carbon Chains: A Formal Formylation of Non‐Acidic C(sp3)−H Bonds

Abstract: A photo‐induced substitutive introduction of an aldoxime functional group to carbon chains was achieved using photo‐excited 4‐benzoylpyridine as a C(sp3)−H bond cleaving agent and arylsulfonyl oxime as an aldoxime precursor. The non‐acidic C−H bonds in various substances, including cycloalkanes, ethers, azacycles, and cyclic sulfides, were chemoselectively converted at ambient temperature under neutral conditions. The present transformation is a formal formylation of non‐acidic C(sp3)−H bonds in a single step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Zard[13c] has explored lauroyl peroxide mediated allylation of xanthate esters with α‐substituted allylic alkyl sulfones, which suggests it should be possible to use sulfones. Furthermore, more recently Ollivier, Kamijo, Zhu, Chen and Flechsig have shown that photocatalytically generated radicals can react with a range of sulfonyl reagents which are capable of trapping radicals, suggesting that it might be possible to identify a prenyl transfer reagent capable of working under photocatalytic conditions. Thus, we synthesized and tested a library of isoprenyl sulfones ( 1j – 1q ).…”
Section: Resultsmentioning
confidence: 99%
“…Zard[13c] has explored lauroyl peroxide mediated allylation of xanthate esters with α‐substituted allylic alkyl sulfones, which suggests it should be possible to use sulfones. Furthermore, more recently Ollivier, Kamijo, Zhu, Chen and Flechsig have shown that photocatalytically generated radicals can react with a range of sulfonyl reagents which are capable of trapping radicals, suggesting that it might be possible to identify a prenyl transfer reagent capable of working under photocatalytic conditions. Thus, we synthesized and tested a library of isoprenyl sulfones ( 1j – 1q ).…”
Section: Resultsmentioning
confidence: 99%
“…The α‐amino functionalization of morpholines via a radical mediated photo‐induced coupling, was initially developed by the Hoffmann group and then explored further by Kamijo and co‐workers. These reactions require the photoactive reagent either in catalytic (Scheme B−D) or stoichiometric (Scheme E) amounts. However, the need for 5 to 8 equivalents of the morpholine coupling partner is the main disadvantage of these methods, limiting their potential wider use in drug discovery projects.…”
Section: Synthesis Of Morpholinesmentioning
confidence: 99%
“… A direct photo‐catalyzed C−H vinylation ( A ) and examples of photoredox α‐amino functionalization methodologies ( B – E ). Reagents and conditions : a) Ir[dF(CF3)ppy]2(dtbbpy)PF6 (1 mol %), CsOAc, DCE, 26 W fluorescent light, rt (yield: 79 %); b) 4,4’‐dimethoxybenzophenone (10 mol %), hv (350 nm), dithiocarbamate, MeCN (yield: 70 %); c) 5,7,12,14‐pentacenetetrone (5 mol %), hv (365 nm LED lamp), K 2 CO 3 , rt, 24 h (yield: 60 %); d) 2‐chloroanthraquinone (10 mol %), hv (365 nm Hg lamp), DCM, rt, 4 h (yield: 48 %); e) Ph 2 CO (1 equiv), hv (medium pressure Hg lamp), t ‐BuOH, rt, 1 h (yield: 98 %)]; (Bn: benzene).…”
Section: Synthesis Of Morpholinesmentioning
confidence: 99%
See 2 more Smart Citations